Acquired Urinary Bladder Diverticulum Secondary to Trauma in German Shepherd Dog: A Case Report - Chukaeo, Chutima; Sutthikan, Somchin; Suraruji, Nattachai (Journal of Mahanakorn Veterinary Medicine, 2020)
A 3-year-old male German Shepherd was referred to hospital with dysuria for a week. The dog was hit by motorcycle 3 months ago. Physical examination showed normal. Abdominal plain radiograph revealed unremarkable. Pneumocystography with room air 200 ml revealed a diverticulum that filled with air at caudodorsal of urinary bladder. Abdominal ultrasound with injected 0.9% NSS to urine catheter revealed a diverticulum at caudodorsal of urinary bladder, thus acquired urinary bladder diverticulum was diagnosed. Surgical correction by diverticulectomy and medical treatment with Enrofloxacin, Tramadol and Firocoxib and urine catheterization. After treatment for 2 weeks, the dog was complete remission.